2020
DOI: 10.1002/alz.12154
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fatty acids and risk of Alzheimer's disease and related dementias: Observations from the Washington Heights‐Hamilton Heights‐Inwood Columbia Aging Project (WHICAP)

Abstract: Introduction: High dietary intake of long chain, polyunsaturated fatty acids is associated with lower Alzheimer's disease (AD) risk. Methods: Washington Heights-Hamilton Heights-Inwood Columbia Aging Project is a multiethnic, prospective observational study of aging and dementia among elderly (≥ 65 years). Dietary intake was measured using a food frequency questionnaire. Dietary short-, medium-, and long-chain fatty acid intakes were categorized by number of carbons and double bonds. Consensus AD diagnoses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 47 publications
0
40
0
2
Order By: Relevance
“…As we know, PSO is rich in ω−3 PUFAs, which is considered to be associated with a lowered risk for AD 43 . Especially, EPA and DHA, two well‐known long‐chain PUFAs, are protective against AD development and related dementias 44 . Some clinical studies demonstrated that the oral ω−3 PUFAs supplementation could retard cognitive deterioration in mild AD patients 45 .…”
Section: Discussionmentioning
confidence: 99%
“…As we know, PSO is rich in ω−3 PUFAs, which is considered to be associated with a lowered risk for AD 43 . Especially, EPA and DHA, two well‐known long‐chain PUFAs, are protective against AD development and related dementias 44 . Some clinical studies demonstrated that the oral ω−3 PUFAs supplementation could retard cognitive deterioration in mild AD patients 45 .…”
Section: Discussionmentioning
confidence: 99%
“…No association between n3 PUFAs and AD was also observed by other authors [ 11 ]. In a study where FFAs intake was assessed with the use of nutritional questionnaire, the authors indicated a lower risk of AD with an increasing intake of n3 PUFAs such as DHA and EPA [ 12 ]. Dietary intake of n-6 fatty acids was connected with better cognitive functions, but such an observation was not elucidated for other FFAs [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The domination of unsaturated fatty acids (UFA) (71.91 %) over saturated (SFA) (26.96 %) is in accordance with FAO and WHO summary report on recommended dietary intake of FA, [35] hence it can be considered as a good source of FA and used as dietary supplements. Diet rich in UFA and lower in SFA has been related to prevention of AD since UFA are important for cell membrane synthesis, neuronal cell integrity and nervous system in general [36] . In addition, linoleic acid showed strong anti‐neuroinflammatory, anti‐amyloidogenic, and anti‐apoptotic effects, as well as improved neuronal survival and memory deficits in the Aß‐infused mouse model.…”
Section: Resultsmentioning
confidence: 99%
“…Diet rich in UFA and lower in SFA has been related to prevention of AD since UFA are important for cell membrane synthesis, neuronal cell integrity and nervous system in general. [36] In addition, linoleic acid showed strong anti-neuroinflammatory, anti-amyloidogenic, and anti-apoptotic effects, as well as improved neuronal survival and memory deficits in the Aß-infused mouse model. , [37] In comparison, S. hirsutum from Chile showed much lower content of unsaturated linoleic (4.70 %) and oleic acids (1.00 %) [32] than S. hirsutum analyzed in this study (40.00 % and 26.81 %, respectively).…”
Section: Chemical Characterizationmentioning
confidence: 99%